An Analysis of English Course Background on Students’ Speaking Ability at Ma’had Al Jami’ah - Aslihatullatifah; Meisuri; Hidayat, Agus (IJLHE: International Journal of Language, Humanities, and Education, 2025)
Speaking ability is an important component in English language learning that enables students to communicate effectively. This study examines the influence of students' English course background on their speaking ability at Ma'had Al Jami'ah, UIN Raden Intan Lampung. Using a qualitative design, data were collected through interviews, questionnaires, and documentation from ten English Education students who had previous course experience. The data were analyzed through thematic analysis to identify patterns and categories related to course duration, frequency, and teaching methods. The results show that differences in course duration, frequency, and teaching methods affect vocabulary mastery, fluency, and confidence. Intensive camp-based programs that provide daily practice and exposure to English result in greater improvements in speaking skills, while short-term or grammar-focused courses result in limited progress. In addition, the Ma'had environment, which integrates structured language programs and daily use of English, plays a crucial role in strengthening and accelerating students' oral skills. This study concludes that English courses provide a foundation for speaking proficiency, but consistent practice and a supportive environment are the main factors that strengthen students' communicative competence.